Morphological and Mineralogical Characterization of Coastal Soil Samples of Kanyakumari District by FT-IR, XRD, SEM/EDAX - Sajitha, S.S.; Metilda, P.; Jenin, G. Aldous (International Journal of Scientific Research and Management (IJSRM), 2017)
Qualitative analysis was carried out to determine the major and minor constituent minerals present incoastal soil samples collected from west cost of Kanyakumari District, Tamilnadu by FT-IR, XRD andSEM/EDAX techniques. From the IR absorption band and the locations of the different peaks, theminerals were identified with the available literature. In addition to the band positions, the sharpness ofbands was helpful in the identification of mineral components. Identification and estimation ofmineralogical composition were carried out by XRD. XRD technique to yield more information about theminerals. FT-IR and XRD methods were non destructive and can be used in the identification ofmineralogical composition. SEM analysis showed the coastal soil samples have different morphologicalstructures like spherical (Al-Si-O), tubular (Si-O), triangular (Fe-Al-Si-O), platy (Ca-Si-O), nearlyspherical (Fe-Ti-O) and irregular (Ca-Al-Si-O) shapes. Elemental analysis (EDAX) confirmed thepresence of silicon in large quantities than the other oxides such as Al, Ca, Fe and Ti.